2020
DOI: 10.3390/insects11090599
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of the Cigarette Beetle Lasioderma serricorne (Fabricius) to Phosphine, Ethyl Formate and Their Combination, and the Sorption and Desorption of Fumigants on Cured Tobacco Leaves

Abstract: The susceptibility of Lasioderma serricorne to phosphine (PH3), ethyl formate (EF) and their combination (PH3 + EF) was evaluated in this study. Eggs, larvae, pupae and adults were subjected to treatment with fumigants to determine the 90% lethal concentration time (LCt90) values. Treatment with PH3 for 20 h resulted in LCt90 values of 1.15, 1.39, 14.97 and 1.78 mg h/L while treatment with EF resulted in values of 157.96, 187.75, 126.06 and 83.10 mg h/L, respectively. By contrast, the combination of PH3 + EF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Kwon et al [ 26 ] found that treatments with low-dose EF (LCT 50% level) prior to cold treatment increased the efficacy of control of pupae, which was not sufficiently controlled by only cold treatment. A better control result was achieved with a combined treatment of EF and phosphine (PH 3 ) against Lasioderma serricorne (Coleoptera: Anobiidae) at lower concentrations than for EF treatment alone and at lower exposure times than for phosphine treatment alone [ 22 ]. Although combined fumigants were not tested in this study, the combination of EF and PH 3 is worth investigating.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kwon et al [ 26 ] found that treatments with low-dose EF (LCT 50% level) prior to cold treatment increased the efficacy of control of pupae, which was not sufficiently controlled by only cold treatment. A better control result was achieved with a combined treatment of EF and phosphine (PH 3 ) against Lasioderma serricorne (Coleoptera: Anobiidae) at lower concentrations than for EF treatment alone and at lower exposure times than for phosphine treatment alone [ 22 ]. Although combined fumigants were not tested in this study, the combination of EF and PH 3 is worth investigating.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, liquid EF (active ingredient: 99%) is also registered in Korea for use against the same pests as Vapormate ® . Experiments have been conducted using EF as a postharvest fumigant in the US, Australia, New Zealand, and Korea, showing good results [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. serricorne is the insect considered to cause the most damage to tobacco, especially cured tobacco leaves (Kathirvel et al, 2019). L. serricorne damages tobacco by excavating tunnels and holes (Kim et al, 2020). Another tobacco leaf damage that occurs during storage in the warehouse is oily tobacco leaves (see Fig.…”
Section: Identification Of Leaf Damagementioning
confidence: 99%
“…The combination treatment of two fumigants has been reported from a variety of applications due to the complementary features; EF acts quickly at high doses and PH 3 acts slowly at low doses [7,17,18]. To apply the combinational application in quarantine, pineapples and sweet pumpkins were used for controlling two-spotted spider mites and citrus mealybugs in Korea [18,19].…”
Section: Introductionmentioning
confidence: 99%